A case study space personalization satisfaction within physiscal workstations of CTID faculty members, UP Diliman. - Competente, Lawrence Christian D.V (College of Home Economics, University of the Philippines Diliman, 2023)
In previous studies about work environment and user satisfaction, the physical design of a space has been proven to affect the user and their work performance (Bitner, 1992; Wells, 2000). This descriptive study aimed to identify the conditions of the physical workstation and the manifestation of space personalization in selected workstations, and determine the levels of satisfaction of faculty members to the applied workstation personalization. As a qualitative descriptive research, the researcher collected data from four purposively selected faculty members from the Department of Clothing, Textiles, and Interior Design through photo documentation and site observations to describe the workstation conditions, and survey questionnaires to relate their satisfaction levels on the applied space personalization. With the help of three Filipino theories regarding space personalization - sense of privacy (Bonifacio, 1977); workstation organization (De Leon Jr., 2012); and Display of Sentimental Items (Lorenzo, 2015), the study showed results that faculty members who have more applied space personalization have higher satisfaction ratings in the three categories, while respondents with minimal space personalization have lower satisfaction levels. Among the three categories, Display of Sentimental Items was the most common application of space personalization by mode rating in the physical workstation and also received the highest satisfaction mean rating equally tied with Workstation Organization, while results presented Sense of Privacy receiving the lowest mode and mean satisfaction rating from the respondents. The researcher recommends a more comprehensive approach and wider scope of faculty members and workstations for better understanding of physical workstation satisfaction from space personalization.